PERAN GURU DALAM MENANAMKAN KEMAMPUAN EMPATI PADA ANAK USIA 5-6 TAHUN DI TK SANTA MARIA SINTANG - Fransiska Fransiska; Suryameng Suryameng; Yuliana Sumiati (STKIP Persada Khatulistiwa Sintang, 2023)
The aims of this study were to describe: 1) The teacher’s role in instilling empathy in children aged 5-6. 2) Factors that influence in instilling empathy abilities in children aged 5-6, 3) The efforts of teachers in instilling empathy abilities in children aged 5-6. This study uses a qualitative approach with a descriptive form. Data collection techniques used were observation, interview, and document. The subjects in this study consisted of one teacher and nine students of B1 class. The data analysis technique used was Miles and Huberman's data analysis. The results of the study show that: 1) The teacher's role in instilling the ability of empathy in children aged 5-6 has been mastered by students, namely being able to empathize, being a role model, understanding children's negative emotions, revising apologizing, increasing patience, avoiding punishment, and finally fulfilling basic needs of children. 2) Factors that influence in instilling the ability to empathize in children aged 5-6, namely the state of the individual, problems in the process of development and the environment. 3) The teacher's efforts in instilling the ability of empathy for children aged 5-6, namely the teacher used the storytelling method, the lecture method, and the habituation method. The role of the teacher in instilling this empathy ability can occur because interaction, socialization, and provision of positive habituation and the right stimulus through learning methods at school so that the empathic abilities of children aged 5-6 can be well embedded.